Lack of muscle mTOR kinase activity causes early onset myopathy and compromises whole‐body homeostasis. Issue 1 (21st November 2018) - Zhang, Qing; Duplany, Agnès; Moncollin, Vincent; Mouradian, Sandrine; Goillot, Evelyne; Mazelin, Laetitia; Gauthier, Karine; Streichenberger, Nathalie; Angleraux, Céline; Chen, Jie; Ding, Shuzhe; Schaeffer, Laurent; et al.
Abstract: Background: The protein kinase mechanistic target of rapamycin (mTOR) controls cellular growth and metabolism. Although balanced mTOR signalling is required for proper muscle homeostasis, partial mTOR inhibition by rapamycin has beneficial effects on various muscle disorders and age‐related pathologies. Besides, more potent mTOR inhibitors targeting mTOR catalytic activity have been developed and are in clinical trials. However, the physiological impact of loss of mTOR catalytic activity in skeletal muscle is currently unknown. Methods: We have generated the mTORmKOKI mouse model in which conditional loss of mTOR is concomitant with expression of kinase inactive mTOR in skeletal muscle. We performed a comparative phenotypic and biochemical analysis of mTORmKOKI mutant animals with muscle‐specific mTOR knockout (mTORmKO) littermates. Results: In striking contrast with mTORmKO littermates, mTORmKOKI mice developed an early onset rapidly progressive myopathy causing juvenile lethality. More than 50% mTORmKOKI mice died before 8 weeks of age, and none survived more than 12 weeks, while mTORmKO mice died around 7 months of age. The growth rate of mTORmKOKI mice declined beyond 1 week of age, and the animals showed profound alterations in body composition at 4 weeks of age. At this age, their body weight was 64% that of mTORmKO mice ( P < 0.001) due to significant reduction in lean and fat mass. The mass of isolated muscles from mTORmKOKI mice was remarkably decreased by 38–56% ( P < 0.001) as compared with that from mTORmKO mice. Histopathological analysis further revealed exacerbated dystrophic features and metabolic alterations in both slow/oxidative and fast/glycolytic muscles from mTORmKOKI mice. We show that the severity of the mTORmKOKI as compared with the mild mTORmKO phenotype is due to more robust suppression of muscle mTORC1 signalling leading to stronger alterations in protein synthesis, oxidative metabolism, and autophagy. This was accompanied with stronger feedback activation of PKB/Akt and dramatic down‐regulation of glycogen phosphorylase expression (0.16‐fold in tibialis anterior muscle, P < 0.01), thus causing features of glycogen storage disease type V. Conclusions: Our study demonstrates a critical role for muscle mTOR catalytic activity in the regulation of whole‐body growth and homeostasis. We suggest that skeletal muscle targeting with mTOR catalytic inhibitors may have detrimental effects. The mTORmKOKI mutant mouse provides an animal model for the pathophysiological understanding of muscle mTOR activity inhibition as well as for mechanistic investigation of the influence of skeletal muscle perturbations on whole‐body homeostasis.